Two’s company, three’s a crowd: Social situations alter group dynamics in the maritime earwig (Anisolabis maritima) - Michael Nolan-Tamariz; Vikram K. Iyengar (PLoS ONE, 2026)
Sexual selection can lead to dimorphic traits that can affect an individual’s behavior including how individuals respond to different social situations. We examined how sex and body size influence aggression and courtship in different-sized groups of the maritime earwig, Anisolabis maritima (Order Dermaptera), an insect in which males and females differ morphologically and behaviorally. In this study, we videotaped mixed-sex pairs and trios of earwigs for two hours to determine the effects of sex and size on their interactions. We found that, in pairs, females were more aggressive than males and both sexes show size-based aggression. However, sex was a stronger determinant of aggression in male-biased trios whereas sex and size were more important in female-biased trios. Male size did not affect courtship in pairs, as large and small males were equally likely to engage in copulatory activity. The presence of intrasexual selection altered the results in the two types of trios. In male-biased trios, the larger male had more copulatory opportunities as his size relative to his rival increased, indicating that intrasexual domination by larger males can overcome female preferences for smaller males observed in previous studies. Interestingly, in female-biased trios, there were no such patterns since copulatory opportunities were relatively rare, the likely result of elevated aggression with two interacting females. Our results indicate that sex and size affect both aggression and sexual behavior differently based on group size and composition, which highlights the need to examine behaviors in a variety of social contexts.